Structural Equation Model Analysis of HIV/AIDS Knowledge, Attitude, and Sex Education Among Freshmen in Jiangsu, China - Tu, Fulai; Yang, Ruizhe; Li, Rui; Du, Guoping; Liu, Yangyang; Li, Wei; Wei, Pingmin (Frontiers in Public Health, 2022)
The study of acquired immunodeficiency syndrome (AIDS) related knowledge, attitude and sex education status of Jiangsu freshmen was conducted, which can provide data support directionally for the prevention work of HIV/AIDS among this populations Male students (4006) and female students (4279) were selected from 20 universities or colleges in Jiangsu province. The knowledge, attitudes and sex education of freshmen was conducted with an online questionnaire. Log-binomial regression model was used to analyze the influencing factors of HIV/AIDS knowledge. In addition, a structural equation model was used to analyze students' health needs which affect knowledge awareness and knowledge mastery. The overall awareness rate of AIDS knowledge was 87.4%. The students in undergraduate colleges (OR=2.523, 95%CI=2.223 2.864) and in independent colleges (OR=1.389, 95%CI=1.172 1.646) were more likely to have a higher awareness compared to the students in junior colleges. In this study, 2011 freshmen approved of premarital behavior, 4921 freshmen insisted on using condoms when having sex, and 8138 freshmen were willing to take HIV antibody test when they suspected they were infected. 4703 freshmen believed that sexual health education was necessary in colleges and universities, and most of them (57.2%) hoped that sex education in schools should be improved. The direct effect of sex education on knowledge awareness and attitude is 0.15 and 0.58. The mediation effect test found that the pass ability knowledge path of sex education indirectly affected sexual attitudes (0.05). The awareness rate of HIV/AIDS among Jiangsu freshmen has not reached the national standard. Health education has a significant positive effect on knowledge awareness and attitude, however, students’ needs in terms of time, place and degree of sex education have not been met in time. It is necessary to strengthen the HIV/AIDS health education of college students in multiple ways.